An HDR (hypoparathyroidism, deafness, renal dysplasia) syndrome locus maps distal to the DiGeorge syndrome region on 10p13/14. Issue 1 (1st January 2000) - Lichtner, Peter; König, Rainer; Hasegawa, Tomonobu; Van Esch, Hilde; Meitinger, Thomas; Schuffenhauer, Simone
Abstract : Partial monosomy 10p is a rare chromosomal condition and a significant proportion of patients show features of DiGeorge syndrome (DGS) and velocardiofacial syndrome (VCFS). A critical haploinsufficiency region for DGS/VCFS was defined on 10p ( DGCR2 ). We performed molecular deletion analysis of two further patients with partial monosomy 10p, who showed hypoparathyroidism, deafness, and renal dysplasia or renal insufficiency, but no cardiac defect, cleft palate, or reduced T cell levels. Previously, the combination of hypoparathyroidism, deafness, and renal dysplasia has been proposed to represent a specific syndrome (MIM 146255) under the acronym HDR. In addition to the two patients in this report, at least four published cases with partial monosomy 10p show the triad of HDR and 14 other patients present with at least two of the three features. We therefore conclude that HDR syndrome can be associated with partial monosomy 10p. Based on molecular deletion analysis and the clinical data, we suggest that the DGS/VCFS phenotype associated with 10p deletion can be considered as a contiguous gene syndrome owing to haploinsufficiency of two different regions. Hemizygosity of the proximal region, designated DGCR2, can cause cardiac defect and T cell deficiency. Hemizygosity of the distal region, designated HDR1, can cause hypoparathyroidism and in addition sensorineuronal deafness and renal dysplasia/insufficiency or a subset of this triad.